Analisis Nilai Tambah Produk Rumah Potong Hewan (Studi Kasus RPH Kategori I dan RPH Kategori II) - Juhari, F.; Nuraini, H.; Cyrilla, L. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
Abattoir categories I and II have different handling processes, abattoir category I without chilling facilites to produce hot carcass and abattoir category 2 with chilling facilities to produce chilled carcass . The objective of this study was to analyze the added value generated in abattoir category I and in abattoir category II, as well as to analyze the factors that affect the amount of added value. This study calculated the amount of added value that abattoir Category I and II could create using Hayami Method. The obtained results showed that abattoir category II produced added value of Rp 44 358 and Rp 45 489 per 1 kg of carcass and Rp 6 552 and Rp 7 022 per 1 kg edible offal, while in abattoir category I the produced added value was much lower that is equal to Rp 25 924 and Rp 25 072 per 1 kg carcass and Rp 3 097 and Rp 4 361 per 1 kg edible offal. The difference of this added value was caused by several factors, one of the most influential factor was the selling price of the product value, in abattoir category II there wasa process of foraging meat (chilling), cooling and packaging of meat divided into Prime Cut, Secondary Cut , Bone, and By Product.